2020
DOI: 10.1002/pbc.28695
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumor in Africa: A systematic review of management challenges and outcome in two decades (2000‐2019)

Abstract: We performed a systematic review to highlight trends in management and outcome of Wilms tumor (WT) in Africa in the past two decades (2000-2019). Twenty-seven studies involving 2250 patients were analyzed. Overall, barring regional variations, 57.7% of the cases presented with advanced disease, 57.3% completed planned treatment, and survival was 56.5%. The publications in the two decades did not show significant differences in proportions of cases with advanced disease, completion of treatment rate, and cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…A recent systematic review on treatment outcomes in eastern African patients with WT showed that OS adjusted for abandonment in 2010-2019 was 46.1% (range 25%-63.2%), which corresponds to survival rates seen in our study. 30 In the Collaborative Wilms Tumor Project, however, EFS was higher than in our study (respectively, 69% compared to 43.5%), but they excluded patients with bilateral tumors. 9…”
Section: Discussioncontrasting
confidence: 80%
“…A recent systematic review on treatment outcomes in eastern African patients with WT showed that OS adjusted for abandonment in 2010-2019 was 46.1% (range 25%-63.2%), which corresponds to survival rates seen in our study. 30 In the Collaborative Wilms Tumor Project, however, EFS was higher than in our study (respectively, 69% compared to 43.5%), but they excluded patients with bilateral tumors. 9…”
Section: Discussioncontrasting
confidence: 80%
“…Between 2016-2021, two-year OS among patients with Wilms tumor was 48%, consistent with contemporary outcomes in the low-resource settings of sub-Saharan Africa. 23 During this period, regional OS ranged from 0-53% at approximately three years, averaging 44% and 27% in East and West Africa, respectively. Survival reported here is similar to that reported by Queen Elizabeth Central Hospital in Blantyre, Malawi where 2-year OS and EFS was 46%.…”
Section: Discussionmentioning
confidence: 90%
“…8 By comparison, OS in relatively high-income South Africa averaged 76% during the same period. 23 In the most recent SIOP and COG reports from high-income countries, OS was >80% across all risk groups, approaching 100% in low-risk disease. 4,16,24…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 The proportion of mortality due to treatment-related neutropenic complications and sinusoidal obstruction syndrome (SOS) is as high as 5%-25% in studies from LMIC. 4,5 Additionally, up to 25% of survivors experience late effects due to the cytotoxic therapy administered for the treatment of WT. 6 Hence, there is a need to identify prognostic factors that can be used to improve the risk-stratification system and stratify candidates for intensive and de-escalated therapy.…”
Section: Introductionmentioning
confidence: 99%